Three-phase controlled rectifier using thyristor / Nur Azmiza Awang - Awang, Nur Azmiza (2004)
Today, the application of power electronics for the control and conversion of electric power is well accepted. Power electronic is based on the switching of power semiconductor devices whose power handling capabilities and switching speeds have improved tremendously over the years. This thesis presents the effects of changing the firing angles of the converter using the power semiconductor switches, i.e thyristors with the DC machine as load. The effects of the firing angles considered are 30°, 60°, 90°, 120° and 150°. In the thesis presented, the converter output is processed by MATLAB software with simulink blocks that can completely show the results. The simulation results which done, the current and voltage waveforms are shown on the scope blocks.